TEL-AML1 regulation of survivin and apoptosis via miRNA-494 and miRNA-320a - Diakos, Christofer (American Society of Hematology, 2010)
There is increasing evidence that miRNA and transcription factors interact in an instructive fashion in normal and malignant hematopoiesis. We explored the impact of TEL-AML1 (ETV6-RUNX1), the most common fusion protein in childhood leukemia, on miRNA expression and the leukemic phenotype. Using RNA interference, miRNA expression arrays, and quantitative polymerase chain reaction, we identified miRNA-494 and miRNA-320a to be up-regulated upon TEL-AML1 silencing independently of TEL expression. Chromatin immunoprecipitation analysis identified miRNA-494 as a direct miRNA target of the fusion protein TEL-AML1. Using bioinformatic analysis as well as functional luciferase experiments, we demonstrate that survivin is a target of the 2 miRNAs. miRNA-494 and miRNA-320a were introduced to the cells by transfection and survivin expression determined by Western blot analysis. These miRNAs blocked survivin expression and resulted in apoptosis in a similar manner as TEL-AML1 silencing by itself; this silencing was also shown to be Dicer-dependent. miRNAs-494 and -320a are expressed at lower levels in TEL-AML1+ leukemias compared with immunophenotype-matched nonTEL-AML1 acute lymphoblastic leukemia subtypes, and within TEL-AML1+ leukemias their expression is correlated to survivin levels. In summary our data suggest that TEL-AML1 might exert its antiapoptotic action at least in part by suppressing miRNA-494 and miRNA-320a, lowering their expression causing enhanced survivin expression.